2023
DOI: 10.3390/life13030697
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Lupus Erythematous and Obstructive Sleep Apnea: A Possible Association

Abstract: Marked fatigue is common in patients with systemic lupus erythematosus (SLE). This study aimed to assess the association of sleep disorders, including obstructive sleep apnea (OSA), with SLE. Forty-two consecutive patients with SLE and 20 healthy controls were recruited and underwent a one-night ambulatory sleep examination. They completed questionnaires, including the Pittsburgh Sleep Quality Index (PSQI) and Functional Assessment of Chronic Illness Therapy (FACIT). SLE disease activity and damage were assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…Previous investigations revealed that SLE patients had lower sleep efficiency compared to healthy controls and higher sleep latency, greater levels of sleep fragmentation, more arousals, more awake time at night . Meidan et al [16] investigated the sleep disturbance in SLE patients and healthy controls. They discovered that the AHI, ODI, and RDI scores in the SLE group were higher than those in the control group (9.2 ± 6.8 vs. 3.9 ± 3.5, p = 0.004, 2.5 ± 2.7 vs. 1.3 ± 1.4, p = 0.04 and 13.5 ± 6.5 vs. 9.7 ± 3.6, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations revealed that SLE patients had lower sleep efficiency compared to healthy controls and higher sleep latency, greater levels of sleep fragmentation, more arousals, more awake time at night . Meidan et al [16] investigated the sleep disturbance in SLE patients and healthy controls. They discovered that the AHI, ODI, and RDI scores in the SLE group were higher than those in the control group (9.2 ± 6.8 vs. 3.9 ± 3.5, p = 0.004, 2.5 ± 2.7 vs. 1.3 ± 1.4, p = 0.04 and 13.5 ± 6.5 vs. 9.7 ± 3.6, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Не виключенням є і СЧВ, ризик його розвитку у жінок з хронічним недосипанням та депресією є втричі вищим порівняно з жінками із достатньою тривалістю сну [4]. Повідомляється, що у хворих на СЧВ проблеми зі сном виявляють у 54%-85% осіб [2,3,9,11]. Інсомнія суттєво знижує якість життя хворих [3,7] та ускладнює перебіг захворювання [3], має високу коморбідність із хронічним больовим синдромом, асоціюється з високою активністю запального процесу [8], втомою, тривогою, депресивними [3] та астенічними розладами [10,11].…”
Section: вступunclassified
“…Подібні закономірності встановлені й щодо індексу важкості захворювання. На думку багатьох дослідників, саме висока активність запального процесу є найбільш визначальною в розвитку інсомнії [4,9,11,14]. За даними [10,15], саме нестача сну свідчить про погіршення активності хвороби.…”
Section: матеріали та методиunclassified